Different joint surgical procedures among thoroughbred horses at Perak Turf Club (PRTC) in association to the race performance from year 2008 to 2015 - Abdul Halim, Hikma Hashiqin (2016)
Locomotion problems and joint injuries are the main cause of early retirement in athletic horses. A retrospective study on cases of equine joint surgeries at Perak Turf Club (PRTC) from year 2008 to 2015 was carried out to define the occurrence and frequency rates in relation to the prognosis. Relationships between duration to first start and number of races after surgery, and frequency of lifespan races with its contributing factors were determined. Records were acquired from equine surgery log book in Veterinary Hospital PRTC and races performances were attained from the Malayan Racing Association (MRA) website. Twenty-five percent (218 joint surgeries out of 849 surgery cases) were identified within the 8-years period. Highest occurrence of joint surgeries was arthroscopic surgery; 83 % (181/218 cases) with the utmost rate was at the right carpal joint (34 %). Carpal joint arthroscopic surgery contributed 81 % of the cases while fetlock joint was only 18 %. From 218 horses, 135 horses had at least one start after the surgery with the median number of days to the start was 180 days. Eighty-eight horses were identified to have successfully raced with median; 6 races and 3 horses recorded more than 30 races after the surgery. The life span average race was 15 years; 54 horses (25 %) had 16 races. There was a relationship between age group with different joint locations. As a conclusion, horses that underwent arthroscopic surgery have a good prognosis and it has the ability to restore racing capability of the horse with high number of races post-operative. The prognosis is contributed by age and lesion at different joint locations. Arthroscopic surgery is suggested to be the best treatment for joints.